Like Attracts Like? The Effects of Anxiety, Implicit Bias, and Perception of Diversity Culture on Team Attraction - Yao, Donna; Chao, Melody M.; George, Elizabeth; Chattopadhyay, Pritviraj (UI Scholars Hub, 2022)
Past relational demography research has demonstrated the influence of demographic dissimilarity among employees on their work engagement and attrition. Little is known about how demographic dissimilarity affects individuals’ attraction to a team in the first place. The present research focused on the attraction component of the attraction-selection-attrition model to investigate factors that contribute to team attraction and their associated underlying processes. Specifically, we identified anxiety towards potential teammates as an affective response to cultural dissimilarity, which in turn influenced performance expectations and team attraction. We also examined implicit and explicit cognitions that might shape the impact of anxiety. To this end, we tested the effects of implicit bias and perceptions of diversity culture in moderating the impact of anxiety on expected team performance and team attraction. Across two experiments, we found that anxiety mediated the effects of cultural dissimilarity on team attraction and performance expectations. Implicit bias, although not influencing the outcomes directly, moderated the link between anxiety and expected team performance. This effect was further moderated by whether diversity was valued. Specifically, when valuing diversity, individuals with heightened anxiety and lower implicit biases had lower expectations of performance from teams with dissimilar (vs. similar) members.